Black Light Express - Reeve, Philip (Railhead ; [2], 2017)
Zen Starling, a small-time thief, and Nova, an android girl come from the Network Empire, whose stations are scattered across the galaxy and linked by the K-gates and the sentient trains travel at light speed between them--but the gate through which they just passed was a new one, and they have no way of knowing into what danger it might have led them.